L' accompagnement spirituel en soins palliatifs, en contexte de Covid-19: analyse de la signification d’une expérience vécue - Barreau, Jean-Marc (Théologiques, 2020)
The Covid-19 pandemic has surprised all mankind with its virulence and impetuosity. The palliative culture has not been spared. Thus, this article, written by two authors, aims to analyze the profound meaning of the experience of spiritual accompaniment that one of the two authors lived, in palliative care, in the midst of the health crisis of the Covid-19 pandemic and whose he offers the story. To provide the scientific basis for the paper, the method of analysis, adopted in this case study, was a qualitative phenomenological approach. Based on the Relational Caring Inquiry, provided by the second author, this phenomenological method offers a relational, dialogical, transformative, and caring approach. Rooted in the narrative, three themes emerge specifically from the analysis: (1) The violence of a forced isolation (healthcare, social, cultural, and spiritual) ; (2) the emergence of a new type of fragilities ; (3) the disintegration of the very principles of palliative science. Rich of this themes, linked in a systemic way, the analysis leads to the emergence of the very essence of the phenomenon in these terms: when palliative science is defined by its capacity to wholly accompany the fragile patient, the suspension of such support during a pandemic seems to conquest the palliative ethos. Finally, the conclusion of this article offers the palliative culture relevant transverse perspectives that could even serve and inspire our healthcare system.